IMPLEMENTING TRADITIONAL FOOD OF MALUKU IN TEACHING PROCEDURE TEXT FOR THE TENTH GRADE OF SMK NEGERI 1 AMBON - Moureen Sherly Latupapua (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2018)
The purpose of this research was to measure how to implement traditional food of Maluku in reading comprehension for understanding procedure text in English. This research was the kind of action research where the writer tried to collaborate her idea with the English teacher of the tenth grade of SMKNegeri 1 Ambon.In gaining the data of his research in 2018/2019 Academic year, there were 27 students at that grade as the subjects of this research. In implementing this strategy, there were four meeting which could be devided in two cycles. Each cycle had two meetings. At the end of each cycle the writer gave the students post test to measure how well they undertood about the procedure texts related to the traditional food of Maluku. The result showed that, there were significant improvement from the first cycle to the second one. In cycle I, there were 27 students who attended the test, 15 of tem or 56% were competent while 12 others or 44% still needed reinforcment. The mean score was 77. According to the successfull indicator, this research should be continued to the Cycle II. Comparing to the Cycle I, Cycle II improved significantly. From 27 students who attended the test, 25 students or 93% were competent while other 2 or 7% still needed reinforcement while the mean score was 87. Based on this result,the writer found out that the reading achievemeent of tenth graders of SMK Negeri 1 Ambon was highly improved. It proved that the students’ understanding of procedure text text well toward traditional food of Maluku